HOXB9 blocks cell cycle progression to inhibit pancreatic cancer cell proliferation through the DNMT1/RBL2/c-Myc axis. (1st May 2022) - Yao, Yang; Liu, Chao; Wang, Bojun; Guan, Xin; Fang, Lin; Zhan, Fei; Sun, Haoxiu; Li, Hengzhen; Lou, Changjie; Yan, Feihu; Lu, Xiaolin; Cui, Luying; et al.
Abstract: Homeobox B9 (HOXB9) is involved in the occurrence and development of malignant tumors. However, the functions and underlying molecular mechanisms of HOXB9 in pancreatic cancer have yet to be identified. In this study, we find that both HOXB9 mRNA and protein levels are down-regulated in pancreatic cancer tissues and cell lines. Kaplan–Meier survival plots of 150 pancreatic cancer cases show that higher expression of HOXB9 in pancreatic cancer patients is associated with higher survival rates. We also find that over-expression of HOXB9 inhibits pancreatic cancer cell proliferation both in cell lines and the nude mouse xenograft as well as PDX models. Applying cell cycle PCR array analysis, Flow CytoMetry, ChIP-qPCR, and luciferase experiments, we observe that HOXB9 blocks cell cycle progression in the G0/G1 phase via up-regulating RBL2 and inhibiting c-Myc, and we further find that DNMT1 inhibits the expression of HOXB9 in pancreatic cancer by promoting the methylation of its promoter. Our findings highlight a novel mechanism of the DNMT1/HOXB9/RBL2/c-Myc pathway in regulating the cell cycle and proliferation of pancreatic cancer cells and provide a research basis for the prognosis and therapeutic application of HOXB9 in pancreatic cancer. Highlights: Pancreatic cancer patients with higher expression of HOXB9 have a better prognosis. HOXB9 blocks cell cycle progression in the G0/G1 phase via up-regulating RBL2 and inhibiting c-Myc. In pancreatic cancer, DNMT1 methylated HOXB9 and down-regulated its expression.